2017
DOI: 10.1186/s13568-017-0377-2
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate decreases methane production also by increasing methane oxidation through stimulating NC10 population in ruminal culture

Abstract: Studies proved that addition of nitrate in rumen could lead to reduction of methane emission. The mechanism of this function was involved in the competition effect of nitrate on hydrogen consumption and the inhibitory effect of generated nitrite on methanogen proliferation. The present study investigated an alternative mechanism that denitrifying anaerobic methane oxidizing (DAMO) bacteria, DAMO archaea and anammox bacteria may co-exist in rumen, therefore, more methane can be oxidized when addition of nitrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 34 publications
5
24
0
Order By: Relevance
“…The percentage of protozoal N derived from bacterial N is low in the current study, probably because of feed N contamination of protozoal samples; thus, protozoal 15 N enrichment was diluted and could not be fixed (data not shown) by the boiling approach described by Ye et al (2018). Although the potential for denitrification of nitrates to N 2 or N 2 O has also been speculated to become a more prevalent route of NO 2 − reduction while CH 4 emission is suppressed (Liu et al, 2017), Latham et al (2016) summarized denitrification to be minor in the rumen but suggested that such alternative routes deserve future research. The lack (P > 0.15) of treatment effect on bacterial N flow or bacterial N derived from NH 3 -N does not support decreased NH 3 -N assimilation.…”
Section: Nitrogen Outflow To Effluentmentioning
confidence: 66%
“…The percentage of protozoal N derived from bacterial N is low in the current study, probably because of feed N contamination of protozoal samples; thus, protozoal 15 N enrichment was diluted and could not be fixed (data not shown) by the boiling approach described by Ye et al (2018). Although the potential for denitrification of nitrates to N 2 or N 2 O has also been speculated to become a more prevalent route of NO 2 − reduction while CH 4 emission is suppressed (Liu et al, 2017), Latham et al (2016) summarized denitrification to be minor in the rumen but suggested that such alternative routes deserve future research. The lack (P > 0.15) of treatment effect on bacterial N flow or bacterial N derived from NH 3 -N does not support decreased NH 3 -N assimilation.…”
Section: Nitrogen Outflow To Effluentmentioning
confidence: 66%
“…The copy number of each standard plasmid was calculated using as described by Yu et al (2005), and the DNA standard calibration curve was made. The 16S rDNA copy numbers of cellulolytic species and total bacteria were calculated as by Zhao et al (2013), and Liu et al (2017). The real-time PCR was performed on ninety-six-well optical plates using CFX96TM Bio-Rad-IQ5 PCR System (Bio-Rad, Lab, Inc, Hercules, USA), was used for PCR assays with SYBR Green Dye Premix Ex Taq™II (Takara, Dalian, Liaoning, China).…”
Section: Methodsmentioning
confidence: 99%
“…The bacteria specific primer sets were shown in Table 2 . The qPCR plasmid standard was prepared according to the method described in a previous study (Liu et al, 2017a ). After that, the concentration of plasmid standards of C .…”
Section: Methodsmentioning
confidence: 99%